Changing epidemiology of influenza and other respiratory viruses in the first year of COVID-19 pandemic. Issue 9 (September 2021) - Agca, Harun; Akalin, Halis; Saglik, Imran; Hacimustafaoglu, Mustafa; Celebi, Solmaz; Ener, Beyza
Abstract: Introduction: We aimed to determine the epidemiological change in influenza and other respiratory tract viruses isolated from patients with nasopharyngeal swab samples in our hospital during the COVID-19 period. Methods: We investigated nasopharyngeal swabs for respiratory viruses between March 2020 and February 2021 during the first year of pandemic in Turkey. We used QIAStat Dx Respiratory panel (Qiagen, Germany) in QIAStat Dx (Qiagen, Germany) for detection of respiratory viruses between March 2020 and February 2021. Respiratory panel kit included influenza A, B, influenza A H1N1, rhinovirus/enterovirus, parainfluenza (PIV) 1, 2, 3, 4, coronaviruses (CoVs) NL 63, 229E, OC43 and HKU1, human metapneumovirus (MPV) A/B, bocavirus, respiratory syncytial virus (RSV) A/B and adenovirus. Results: We retrospectively analyzed the results of 319 nasopharyngeal swab samples. The average age of 199 (62.4%) male and 120 (37.6%) female patients between the ages of 0–92 was 16 years. We found that 101 (31.7%) samples were positive for viruses. Rhino/enteroviruses were the most common viruses in all age groups. Influenza positivity rate during the first year of pandemic declined to 2.3% from 17.3% among the previous year. MPV infection activity did not change during the pandemic. Discussion: According to our findings we argue that epidemiology of respiratory viruses has changed during the pandemic period. Despite the current clinical focus on the COVID-19 pandemic, clinicians should keep in mind that rhino/enterovirus and MPV infections may mimic COVID-19 and respiratory infections should be differentially diagnosed with rapid multiplex kits containing SARS-CoV-2, rhino/enterovirus and MPV.